Propuesta de aprovechamiento de agua lluvia en el casco urbano del municipio de Tenjo, Cundinamarca (2020)
Assigning a use of rainwater runoff, as is the purpose of the EmserTenjo company, required creating a traceability route analyzing the physicochemical composition of rainwater, to study the different alternatives for use, and from there, select the most appropriate one to adapt this resource, through a treatment to improve the quality of rainwater, and finally, estimate the respective costs of the proposal. The development consisted of obtaining the diagnosis of rainwater by runoff experimentally in the study area, complemented by bibliographic reviews on characterization of rainwater in areas with geo-demographic characteristics related to the study area. Applying statistical tools (AHP model), the option for the adaptation of rainwater for the agricultural sector was selected as the best alternative for use, comparing with the regulations set forth in Decree 1594 of 1984, the parameters that were out of specification were identified, and who required adequate treatment, they selected two treatment stages; the pre-treatment and primary treatment stage. Finally, the costs of the investment in civil works and equipment, annual operating and maintenance (O&M) expenses of the treatment units were estimated, in order to later establish the viability of the project by determining its benefits.